Radiocarbon and 230Th data reveal rapid redistribution and temporal changes in sediment focussing at a North Atlantic drift - Mollenhauer, Gesine; McManus, Jerry F.; Wagner, Thomas; McCave, I. Nick; Eglinton, Timothy I. (Earth and Planetary Science Letters, 2011)
In locations of rapid sediment accumulation receiving substantial amounts of laterally transported material the timescales of transport and accurate quantification of the transported material are at the focus of intense research. Here we present radiocarbon data obtained on co-occurring planktic foraminifera, marine haptophyte biomarkers (alkenones) and total organic carbon (TOC) coupled with excess Thorium-230 (230Thxs) measurements on four sediment cores retrieved in 1649–2879m water depth from two such high accumulation drift deposits in the Northeast Atlantic, Björn and Gardar Drifts. While 230Thxs inventories imply strong sediment focussing, no age offsets are observed between planktic foraminifera and alkenones, suggesting that redistribution of sediments is rapid and occurs soon after formation of marine organic matter, or that transported material contains negligible amounts of alkenones. An isotopic mass balance calculation based on radiocarbon concentrations of co-occurring sediment components leads us to estimate that transported sediment components contain up to 12% of fossil organic matter that is free of or very poor in alkenones, but nevertheless appears to consist of a mixture of fresh and eroded fossil material. Considering all available constraints to characterize transported material, our results show that although focussing factors calculated from bulk sediment 230Thxs inventories may allow useful approximations of bulk redeposition, they do not provide a unique estimate of the amount of each laterally transported sediment component. Furthermore, our findings provide evidence that the occurrence of lateral sediment redistribution alone does not always hinder the use of multiple proxies but that individual sediment fractions are affected to variable extents by sediment focussing.